TAFSIR TEMATIK AYAT-AYAT ZAKAT DAN SEDEKAH SERTA RELEVANSINYA DALAM KONTEKS KONTEMPORER - Julianti, Anisa (STAI Asy-Syukriyyah, 2025)
The development of the modern workplace has implications for the understanding and practice of social worship in Islam, particularly zakat and alms. While in classical times zakat was more associated with agricultural products, livestock, and certain assets, today the sources of income for Muslims are increasingly diverse, including salaries and professional income. This condition demands a more contextual approach to Islamic law. This study aims to examine the Qur'anic verses on zakat and alms through a thematic interpretation approach and their relevance in the current context. The research method used is content analysis of the Qur'anic verses and the interpretations of commentators, particularly M. Quraish Shihab in Tafsir Al-Misbah. The results of the study indicate that zakat and alms not only function as ritual worship, but also have a strong socio-economic dimension and are adaptive to current developments, including the use of digital technology in their management.